A preliminary study on effect of lactobacillus paracasei hii01 on cortisol in fatigue subjects - Ekasit Lalitsuradej (2020)
© 2019 IEEE. Fatigue is one of health illness issue in the world. It is developed from variety of factors. Stress is believed the main factor that induces fatigue. Stress is not only presented as fatigue symptom but also neuroendocrine alteration. The activation of Hypothalamus-Pituitary-Adrenal Axis (HPA-Axis) by stress impacts to cortisol level and induces inflammatory cytokine secretion. The activation of HPA-Axis induces gut microbiota alteration which is the causes of many mental and physical illnesses. Since stress-induced fatigue, it causes HPA-Axis activation and influences to gut microbiota alteration. Non-pharmacological approaches by probiotics consumption has numerous studies proving benefits on regulating HPA-Axis. The objective of the current study was to investigate benefits of probiotics supplementation (Lactobacillus paracasei HII01) on HPA-Axis by attenuating salivary cortisol level. Seven fatigue subjects (with an average age of 49.14 ± 17.74 years) were supplemented with 12.5 billion cells of L. paracasei HII01 per day for 12 weeks. After 12 weeks of intervention, the changes in cortisol level was calculated. Salivary cortisol level (from 224.07 ± 84.24 to 170.09 ± 63.23 ng/ml) was significantly decreased in the probiotic-supplemented group when compared to the baseline value. According to the results of the current study suggested that the supplementation of L. paracasei HII01 may attenuate salivary cortisol level and further studies are mandatory to reveal the health beneficial effect of the probiotic strain L. paracasei HII01.